Computational screening of zeolites for C3H7Cl/C3H5Cl separation and a conformation based separation mechanism. (10th August 2019) - Zhang, Yujia; Xu, Yinxiang; Xu, Junbo; Yang, Chao
Graphical abstract: Highlights: Zeolites were screened for C3 H7 Cl/C3 H5 Cl separation by molecular simulation. AHT type zeolite shows the best C3 H7 Cl/C3 H5 Cl separation performance. A pore geometry based conformation recognition separation mechanism is proposed. Abstract: The separation of alkanes-olefins plays an essential role in petrochemical industry and is also challenging because of their similar physicochemical properties, especially for halogenated alkanes-olefins mixtures. In this work, we quickly screened a series of zeolites to separate 1-chloropropane/allyl chloride (C3 H7 Cl/C3 H5 Cl) mixture by molecular simulation. The results show that zeolites with specific pore geometry (e.g., AHT type) only adsorb C3 H5 Cl thus C3 H5 Cl can be selectively separated from C3 H7 Cl completely. These zeolites have one-dimensional elliptical pores with similar sizes, which match with the low energy conformation of C3 H5 Cl. The flux data of membrane based on these zeolites were also investigated, which confirmed that they can separate C3 H7 Cl and C3 H5 Cl with an ultrahigh selectivity. Based on the thermodynamics analysis, we proposed a pore geometry based conformation recognition mechanism of this special adsorption and separation phenomena. In conclusion, this paper provides an avenue to design or screen nano-porous materials for alkanes-olefins separation.